Repurposing of Chemotherapeutics to Combat COVID-19 - Nandi, Sisir; Nayak, Bhabani S.; Khede, Mayank Kumar; Saxena, Anil Kumar (Current Topics in Medicinal Chemistry, 2022)
Severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) is a novel strain of SARS coronavirus. The COVID-19 disease caused by this virus was declared a pandemic by the World Health Organization (WHO). SARS-CoV-2 mainly spreads through droplets sprayed by coughs or sneezes of the infected to a healthy person within the vicinity of 6 feet. It also spreads through asymptomatic carriers and has negative impact on the global economy, security and lives of people since 2019. Numerous lives have been lost to this viral infection; hence there is an emergency to build up a potent measure to combat SARS-CoV-2. In view of the non-availability of any drugs or vaccines at the time of its eruption, the existing antivirals, antibacterials, antimalarials, mucolytic agents and antipyretic paracetamol were used to treat the COVID-19 patients. Still there are no specific small molecule chemotherapeutics available to combat COVID-19 except for a few vaccines approved for emergency use only. Thus, the repurposing of chemotherapeutics with the potential to treat COVID-19 infected people is being used. The antiviral activity for COVID-19 and biochemical mechanisms of the repurposed drugs are being explored by the biological assay screening and structure-based in silico docking simulations. The present study describes the various US-FDA approved chemotherapeutics repositioned to combat COVID-19 along with their screening for biological activity, pharmacokinetic and pharmacodynamic evaluation.
Keywords: US-FDA approved chemotherapeutics